USE OF ACTIVE METHODOLOGIES IN THE TRAINING OF HEALTH AND EDUCATION PROFESSIONALS: A STUDY WITH EMPHASIS ON MEANINGFUL LEARNING - Islândia Barbosa Dantas de Meneses, Uberlândia; Evangelista de Sousa, Jackeline; Karina de Almeida Soares, Ana; da Silva Carvalho, Denise; Aparecida Oliveira Pereira, Delciene (Revista Gênero e Interdisciplinaridade, 2026)
The use of active methodologies in the training of health and education professionals has been consolidated as an innovative strategy for transforming teaching-learning processes, especially in the contemporary context marked by complex and dynamic demands. This study aimed to analyze the contributions of active methodologies in professional training, with an emphasis on meaningful learning. This is a theoretical-reflective study based on a critical analysis of scientific literature. The findings indicate that methodologies such as problem-based learning, realistic simulation, collaborative learning, and the use of digital technologies promote student protagonism, integration between theory and practice, and the development of cognitive, technical, and socio-emotional skills. It was observed that these strategies enhance meaningful learning by promoting the connection between prior knowledge and new information, resulting in greater retention, understanding, and applicability of content. However, their implementation still faces challenges, such as teacher resistance, structural limitations, and the need for continuous professional development. It is concluded that active methodologies, when used intentionally and aligned with meaningful learning, contribute to the training of more critical, autonomous, and prepared professionals, highlighting the importance of investing in teacher training and institutional policies that support their consolidation.